ANALISIS PENGARUH PENAMBAHAN LIMBAH PAKU TERHADAP SIFAT MEKANIS BETON NORMAL - Teuku Muhammad Bhima; Muhtarom Riyadi; Lilis Tiyani (Construction and Material Journal, 2022)
The use of steel fibres as a concrete mixture can prevent cracks due to loading, the heat of hydration, and shrinkage. However, the availability of steel fibre is still limited, and it is expensive enough that alternative materials are required, which may reduce the economic value. This research aims to analyse the effect of an easy-to-find alternative material, namely plywood nail waste, on the properties of normal concrete. Concrete properties tests include compressive strength, split tensile strength, flexural strength, and modulus of elasticity. This research was conducted by mixing concrete with nail waste material with variations of 0%, 1%, 1.5%, and 2% of the weight of the concrete. Concrete samples in the shapes of cylinders and beams are required for this study.  The results showed that using nail waste can reduce the compressive strength of 28-day-old concrete and the modulus of elasticity as the variation of the nail waste increases. However, the use of nail waste in certain variations can increase the split tensile strength and flexural strength of concrete. Split tensile strength measurements after adding nail waste with varying amounts of 0%, 1%, 1.5%, and 2% were 2.279 MPa, 2.408 MPa, 2.068 MPa, and 1.583 MPa. The optimum variation was 1%, with an increase of approximately 5.64% of concrete without mixed waste nails. The variation of nail waste also produces flexural strength values of 1.95 MPa, 2.47 MPa, 2.21 MPa, and 1.43 MPa, so the optimum variation is 1%, with an increase of about 26.67% from the concrete without nail waste mixture. Keywords: Normal Concrete, Waste Nail, Mechanical Properties.